Exploring the Items for Measuring Product Development and Commercialization (PDC) in Flexibility of Supply Chain Management in the Manufacturing Companies in Nigeria: An Exploratory Factor Analysis - Naimot Folake Popoola; Popoola Mufutau Olapoju (Research Parks Publishers, 2026)
The aim of this research is to execute instrument validation for the items of product development and commercialization (PDC)through exploratory factor analysis (EFA). The data collection tool employed is questionnaires which was administrated to employees in the manufacturing companies in Nigeria. 100 questionnaires were gathered to do the EFA. The results show that the Bartletts’ Test of Sphericity is significant (P-Value < 0.05), Kaiser-Meyer-Olkin (KMO) is excellent as it exceeds the require value of 0.6 .These two results (Bartlett’s Test is significant and KMO > 0.6) indicate that the data is adequate in size.. The Cronbach’s Alpha test was higher than 0.7 for the all items of the constructs, this suggest that these items are all reliable. This research add to the domain of supply chain management by assessing the items of the construct of product development and commercialization (PDC) that could improve performances in manufacturing organizations in the context of Nigeria.